Selenite reduction and biogenesis of selenium-nanoparticles by different size groups of aerobic granular sludge under aerobic conditions. (15th May 2023) - Sudharsan, G.; Sarvajith, M.; Nancharaiah, Y.V.
Abstract: Microbial transformations play a vital role in Se cycle in the environment and decrease the solubility and toxicity of Se oxyanions by converting to elemental selenium (Se 0 ) nanostructures. Aerobic granular sludge (AGS) has attracted interest due to efficient reduction of selenite to biogenic Se 0 (Bio-Se 0 ) and retention in bioreactors. Here, selenite removal, biogenesis of Bio-Se 0 and entrapment of Bio-Se 0 by different size groups of aerobic granules were investigated to optimize biological treatment process for Se-laden wastewaters. Furthermore, a bacterial strain showing high selenite tolerance and reduction was isolated and characterized. Removal of selenite and conversion to Bio-Se 0 were achieved by all the size groups of granules ranging from 0.12 mm to 2 mm and above. However, selenite reduction and Bio-Se 0 formation were rapid and more efficient with large aerobic granules (≥0.5 mm). The formed Bio-Se 0 was majorly associated with the large granules, due to better entrapment capabilities. In contrast, the Bio-Se 0 formed by the small granules (≤0.2 mm) was distributed both in the granules and aqueous phase because of ineffective entrapment. Scanning electron microscope and energy dispersive X-ray (SEM-EDX) analysis confirmed formation of Se 0 spheres and association with the granules. Efficient selenite reduction and entrapment of Bio-Se 0 was related to prevalent anoxic/anaerobic zones in the large granules. A bacterial strain showing efficient SeO3 2− reduction of up to 15 mM SeO3 2− under aerobic conditions was identified as Microbacterium azadirachtae . SEM-EDX analysis confirmed the formation and entrapment of Se 0 nanospheres (size: 100 ± 5 nm) in the extracellular matrix. The cells immobilized in alginate beads showed effective SeO3 2− reduction and Bio-Se 0 entrapment. Efficient reduction and immobilization of bio-transformed metalloids by large AGS and AGS-borne bacteria implicates prospective use in bioremediation of metal(loid) oxyanions and bio-recovery. Graphical abstract: Image 1 Highlights: Selenite reduction and Bio-Se 0 retention were dependent on size of aerobic granules. Large sized aerobic granules showed efficient selenite reduction and Bio-Se 0 entrapment. Microbacterium azadirachtae isolated from granules exhibited efficient selenite reduction. M. azadirachtae cells immobilized in alginate beads exhibited selenite reduction and Bio-Se 0 entrapment.